2014
DOI: 10.1371/journal.pone.0098663
|View full text |Cite|
|
Sign up to set email alerts
|

Knowing Right From Wrong In Mental Arithmetic Judgments: Calibration Of Confidence Predicts The Development Of Accuracy

Abstract: Does knowing when mental arithmetic judgments are right—and when they are wrong—lead to more accurate judgments over time? We hypothesize that the successful detection of errors (and avoidance of false alarms) may contribute to the development of mental arithmetic performance. Insight into error detection abilities can be gained by examining the “calibration” of mental arithmetic judgments—that is, the alignment between confidence in judgments and the accuracy of those judgments. Calibration may be viewed as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 45 publications
8
55
1
2
Order By: Relevance
“…The present results in combination with previous findings suggest that this trajectory may spread over a more extended period in individuals with ASD, or may remain impaired across the lifespan, which is supported by findings of impaired metamemory and reality monitoring in adults with ASD [Cooper et al, ]. Relatedly, Rinne and Mazzocco [] investigated calibration in mental arithmetic, which is the alignment of accuracy and confidence of judgments. They found that calibration continued to develop through grades 5 to 8, even when arithmetic accuracy neared ceiling.…”
Section: Discussionsupporting
confidence: 86%
“…The present results in combination with previous findings suggest that this trajectory may spread over a more extended period in individuals with ASD, or may remain impaired across the lifespan, which is supported by findings of impaired metamemory and reality monitoring in adults with ASD [Cooper et al, ]. Relatedly, Rinne and Mazzocco [] investigated calibration in mental arithmetic, which is the alignment of accuracy and confidence of judgments. They found that calibration continued to develop through grades 5 to 8, even when arithmetic accuracy neared ceiling.…”
Section: Discussionsupporting
confidence: 86%
“…Problem Verification Task was developed as a measure of math calculation fluency and metacognition (Rinne & Mazzocco, 2014). We relied on the calculation fluency component of this measure in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Problem Verification Task (Rinne & Mazzocco, 2014) was used to measure participants’ math calculation fluency. Description of this task can be found under the Methods section for Study 1.…”
Section: Methodsmentioning
confidence: 99%
“…As longitudinal data by Rinne and Mazzocco (2014) have shown, students who had better metacognitive monitoring ability also had larger gains in performance. Students' ability to estimate their own performance can be measured via metacognitive judgments.…”
mentioning
confidence: 87%